Smoking attitudes and affecting factors of the nurses working in turgut ozal medical center - Aylaz, R.; Hacıevliyagil, S.; Durdu, A. (Journal of Dependence, 2008)
Objective: This study aimed to determine the smoking rate, cigarette addiction status of smokers, and risk factors related to smoking behavior among nurses working in a university hospital. Method: A survey was conducted under observation at Inonu University, Faculty of Medicine, Turgut Ozal Medical Center between June 2006 and August 2006. A questionnaire consisting of socio-demographic characteristics and the Fagerstrom nicotine addiction test was administered to the nurses. Findings: Smoking habit was found to be 54.4% among nurses (42.1% among females, 61.7% among males). Nurses were found to smoke more in hospital settings (59.4%). A significant difference was found between the smoking behavior of nurses according to their educational background (p<0.05). The smoking rate was higher among nurses who graduated from health vocational high schools than among those who graduated from university. Having a family member who smokes was an influence on nurses’ smoking behavior (p<0.05). According to the Fagerström Nicotine Dependence Test, 20% of current smokers were found to have a high level of dependence, while 10% were found to have a very high level of dependence. Conclusion: In this study, 54.4% of nurses smoked, which is a serious health problem. It was determined that nurses smoked more in hospitals and were exposed to secondhand smoke. Individuals providing healthcare services are expected to be more knowledgeable and sensitive about smoking and addiction. Therefore, topics such as smoking and health, and nicotine addiction should be included in the nursing curriculum.